The Role of Dividend Policy as An Intervening of Financial Performance on Company Value - Mia Laksmiwati; Rinny Meidiyustiani; Retno Fuji Oktaviani; Sugeng Priyanto (CV. Ridwan Publisher, 2023)
When investors want to invest in a stock on the stock exchange, the first thing to look at, apart from the company's fundamental performance, is the stock price. One of the ratios that is widely used in making investment decisions is the ratio of stock prices to the company's book value (Price To Book Value). The book value of the company is the value of the company's assets divided by the number of shares issued by the company. In other words, the book value of the shares is the fair value of the issuer's shares, which reflects the company's fundamental performance. This study aims to determine the effect of Firm Size, Financial Leverage, Economic Value Added, Market Value Added on Price to Book Value with Dividend Payout Ratio as an intervening variable. The research subjects are companies that are members of IDX 30 on the Indonesia Stock Exchange during the 2017-2021 period. The method of data analysis is multiple linear regression using R Studio software. The results showed that Firm Size had an effect on the Dividend Payout Ratio. While Financial Leverage, Economic Value Added, Market Value Added have no effect on the Dividend Payout Ratio. Financial Leverage and Market Value Added have an effect on Price to Book Value, but Firm Size and Economic Value Added have no effect on Price to Book Value. Dividend Payout Ratio is only able to mediate Firm Size on Price to Book Value.